TINJAUAN EFEKTIFITAS MEDIA PROMOSI EVENT BUDAYA PACU JALUR KUANTAN SINGINGI - EENG WAHYUDI ARMY, Dr. Budiwirman, M.Pd., Dra. Jupriani, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Tourism in Indonesia today has seen significant improvements in the provision of tourism products, thus increasing the image to be better known as a tourist destination that presents natural beauty and cultural diversity. Along with the development of the world of tourism today, tourism products based on the traditional environment of the community as well as cultural tourism activities such as traditional ceremonies and religious rituals also get special attention for tourists both foreign tourists and local tourists. This study aims to collect data to solve the problems found in this study. While in particular, attraction of race track tradition in Kuantan Singingi regency.The data were collected by survey method with questionnaire. Data analysis technique used in this research is quantitative method with cross sectional. Cross sectional is a study that is used only once to describe the effectiveness of Promotional Media Cultural Events Pacu Jalur Kuantan Singingi. The sampling technique in this research is using accidental sampling technique, that is by giving questionnaires to the respondent who meet the writer in the field. A total of 100 visitors.After doing research and mengprestasikan results of research conducted in Kuantan Singingi. So the researcher can conclude several things that are as follows: 1) The high interest of visitors in witnessing the event tradition of the pathway this thing can be seen on the graph of the development of visitors to kuantan singingi in witnessing the race track, the highest is in 2014 that is as many as 285,000 people. 2) The creativity of the team to create a banner poster for this pathway event has an attractive color and also attractive graphic design.Keywords Media Promotion, Epic Model, Pacu Jalur